Tobacco use among youth and adults in member countries of South-East Asia region: Review of findings from surveys under the global tobacco surveillance system - Dhirendra N Sinha; Krishna M Palipudi; Italia Rolle; Samira Asma; Sonam Rinchen (Wolters Kluwer Medknow Publications, 2011)
Background: This paper examines the prevalence of current tobacco use among youth and adults in selected member countries of the South-East Asia Region using the data from school and household-based surveys included in the Global Tobacco Surveillance System. Materials and Methods: Global Youth Tobacco Survey (GYTS) data (years 2007-2009) were used to examine current tobacco use prevalence among youth, whereas Global Adult Tobacco Survey (GATS) data (years 2009-2010) were used to examine the prevalence among adults. GYTS is a school-based survey of students aged 13-15, using a two-stage cluster sample design, and GATS is a household survey of adults age 15 and above using a multi-stage stratified cluster design. Both surveys used a standard protocol for the questionnaire, data collection and analysis. Results: Prevalence of current tobacco use among students aged 13-15 varied from 5.9% in Bangladesh to 56.5% in Timor-Leste, and the prevalence among adults aged 15 and above was highest in Bangladesh (43.3%), followed by India (34.6%) and Thailand (27.2%). Reported prevalence was significantly higher among males than females for adults and youth in all countries except Bangladesh, Sri Lanka and Timor-Leste. Current use of tobacco other than manufactured cigarettes was notably higher than current cigarette smoking among youth aged 13-15 years in most countries of the Region, while the same was observed among adults in Bangladesh, India and Thailand, with most women in those countries, and 49% of men in India, using smokeless tobacco. Conclusion: Tobacco use among youth and adults in member countries of the region is high and the pattern of tobacco consumption is complex. Tobacco products other than cigarettes are commonly used by youth and adults, as those products are relatively cheaper than cigarettes and affordable for almost all segments of the population. As a result, use of locally produced smoked and smokeless tobacco products is high in the region. Generating reliable data on tobacco use and key tobacco control measures at regular intervals is essential to better understand and respond with effective tobacco control intervention.